The evaluation of malignant astrocytoma score (MAS) - Kojadinović Željko; Vuleković Petar; Jajić Đorđe; Cigić Tomislav; Papić Vladimir; Đilvesi Đula; Horvat Igor; Karan Mladen (Vojnosanitetski Pregled)
Background/Aim. At the moment there are few scoring systems for malignant astrocytoma but they are not widely accepted. The aim of this study was to evaluate malignant astrocytoma score (MAS) on a new group of patients with malignant astrocytoma, to compare MAS with other prognostic tools and to describe the use of MAS in everyday practice in neurooncology. Methods. The study was performed on 124 patients with supratentorial malignant astrocytoma grade III or IV. They were operated on and subsequently irradiated with 50-60 Gy. Results. The mean age of the patients was 57.3 years. The mean Karnofski performance status (KPS) of the functional inpairment was 54. The removal of the tumor > 90% was done in 59.7% of patients. The mean survival was 9.1 months, and 27.4% of patients had a 12-month survival. The area under receiver operating characteristic (ROC) curve (AUC) of the MAS for predicting 6-, 12- and 18-month survival was 0.754, 0.783 and 0.882, respectively. We compared the MAS with the two mostly cited scoring systems. The AUC for the same prediction for medical research council (MRC) was 0.601, 0.693, 0.772 respectively. For the Radiation Therapy Oncology Group (RTOG) the AUC was 0.732, 0.765, 0.827, respectively. Conclusion. MAS represents a useful scoring system for determining illness severity and prognosis in patients with malignant supratentorial astrocytoma. It can be helpful in comparing single patients or groups of patients, as well as results of different treatments and in controlling the quality of hospital treatment and so on.